NATURAL PRODUCTS AS EFFLUX PUMP INHIBITORS ENHANCING THE ANTIBACTERIAL EFFICACY OF QUINOLONES - Mohan Arya; A.R. Nisha; V. Keerthika (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Antimicrobial resistance is a global pandemic and one of the biggest public health challenges. Efflux pumps are one of several antimicrobial resistance mechanisms. Efflux pumps are proteins that act by efflux or pumping substances out of cells. The major efflux pumps in bacteria include the ATP-binding cassette (ABC) Superfamily, Small Multidrug Resistance Family (SMR), Major Facilitator Superfamily (MFS), Multidrug and Toxic Compound Extrusion Family (MATE), and Resistance Nodulation Cell Division (RND). Quinolones are antimicrobials that inhibit DNA synthesis by inhibiting type IV topoisomerase and DNA gyrase of bacteria. Efflux-mediated quinolone resistance can happen by the overexpression of some efflux pump genes in the prokaryotes. The substrate for most of the efflux pumps is fluoroquinolones like ciprofloxacin and Norfloxacin. A novel strategy to combat antimicrobial resistance is by the use of efflux pump inhibitors which can effectively block the efflux pumps. Plant-derived phytochemicals are promising lead molecules in developing an efflux pump inhibiting drug and thereby combat quinolone mediated efflux resistance. This review discusses plant-derived EPIs that can be used to combat quinolone-resistant microorganisms.